On Language and Development in Africa: The Case of Ghana (Nordic Journal of African Studies, 1996)
In their search for solutions to the development problems of Africa, students of African development have often ignored linguistic and other socio?cultural resources (Prah 1993). When linguistic issues are addressed at all, the fact that there is a multiplicity of languages in African countries is often seen as a hindrance to the development of the continent. This paper focuses on the relationship between language and development and offers a specific proposal for addressing issues of language policy and planning in Africa. Taking the language situation in Ghana as a case study, a model of development communication and education termed localized trilingualism is proposed; a model, it is believed, will enable Africa to harness its multilingual resources for accelerated and sustainable socio?cultural, economic and technological development in the 21st century.